2019
DOI: 10.1101/2019.12.19.882878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparative Study of the Turnover of Multiciliated Cells in the Mouse Trachea, Oviduct and Brain

Abstract: In mammals, multiciliated cells (MCCs) line the lumen of the trachea, oviduct, and brain ventricles, where they drive fluid flow across the epithelium. Each MCC population experiences vastly different local environments that may dictate differences in their lifetime and turnover rates. However, with the exception of MCCs in the trachea, the turnover rates of these multiciliated epithelial populations at extended time scales are not well described.Here, using genetic lineage-labeling techniques we provide a dir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Using lineage tracing we showed that the Prom1 expressing population did not expand over time and in the case of the isthmus decreased over the course of the experiment. Taken together our results show that Prom1 does not label a stem or progenitor population in the mouse oviduct.6Multiciliated cell turnover rate in the distal mouse oviduct has been estimated to be around 6 months(25). As we see a near exclusive labeling of multiciliated cells one month after tamoxifen injections we would have expected to see a steady drop in the number of labeled cells over time.…”
mentioning
confidence: 51%
“…Using lineage tracing we showed that the Prom1 expressing population did not expand over time and in the case of the isthmus decreased over the course of the experiment. Taken together our results show that Prom1 does not label a stem or progenitor population in the mouse oviduct.6Multiciliated cell turnover rate in the distal mouse oviduct has been estimated to be around 6 months(25). As we see a near exclusive labeling of multiciliated cells one month after tamoxifen injections we would have expected to see a steady drop in the number of labeled cells over time.…”
mentioning
confidence: 51%